2015
DOI: 10.1016/j.pneurobio.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

3D in vitro modeling of the central nervous system

Abstract: There are currently more than 600 diseases characterized as affecting the central nervous system (CNS) which inflict neural damage. Unfortunately, few of these conditions have effective treatments available. Although significant efforts have been put into developing new therapeutics, drugs which were promising in the developmental phase have high attrition rates in late stage clinical trials. These failures could be circumvented if current 2D in vitro and in vivo models were improved. 3D, tissue-engineered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
188
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(189 citation statements)
references
References 349 publications
(408 reference statements)
0
188
0
Order By: Relevance
“…23,32 The spheroid culture allows for high density, which can mimic in vivo intercellular distance and communication better than scaffold cultures. 1 Cell density in spheroids at 1 DIV (2 · 10 6 cells/ mm 3 ) was approximately one magnitude higher than in vivo density. Cell aggregation in the spheroid can be described as close packing of spheres, 33 thus the initial cell density within the spheroid is dependent on cell size rather than the number of cells per spheroid.…”
Section: Versatile Culturementioning
confidence: 85%
See 3 more Smart Citations
“…23,32 The spheroid culture allows for high density, which can mimic in vivo intercellular distance and communication better than scaffold cultures. 1 Cell density in spheroids at 1 DIV (2 · 10 6 cells/ mm 3 ) was approximately one magnitude higher than in vivo density. Cell aggregation in the spheroid can be described as close packing of spheres, 33 thus the initial cell density within the spheroid is dependent on cell size rather than the number of cells per spheroid.…”
Section: Versatile Culturementioning
confidence: 85%
“…Thus, 3D cultures have typically been limited to extracellular field potential recordings of far lower resolution and generally do not identify neurotransmitter type. 1,16 Here, spheroids can be removed from the hydrogel mold and immobilized on coverslips, making this 3D culture compatible with patch-clamp recording. Wholecell recordings at 14 and 21 DIV showed that the neurons in the spheroids had matured and were able to fire spontaneous and evoked action potentials associated with mature neurons.…”
Section: Active Circuitry In the Spheroidmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and refinement of existing in vitro three-dimension models of BBB, traditionally employed in the screening of drugs or molecule designed to cross the BBB, could be used as a novel approach to investigate the genotype and phenotype of cancer cells that migrate through artifi cial BBBs. [114,115] Also, the previous mentioned breakthrough discovery of the presence of lymphatic vessels in the brain could open an avenue of cutting edge experimental approaches in the study of CTCs and BM.…”
Section: Resultsmentioning
confidence: 99%